1995
DOI: 10.1126/science.7535475
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cytokine Export and Apoptosis in Mice Deficient in Interleukin-1β Converting Enzyme

Abstract: The interleukin-1 beta (IL-1 beta) converting enzyme (ICE) processes the inactive IL-1 beta precursor to the proinflammatory cytokine. Adherent monocytes from mice harboring a disrupted ICE gene (ICE-/-) did not export IL-1 beta or interleukin-1 alpha (IL-1 alpha) after stimulation with lipopolysaccharide. Export of tumor necrosis factor-alpha and interleukin-6 (IL-6) from these cells was also diminished. Thymocytes from ICE-/- mice were sensitive to apoptosis induced by dexamethasone or ionizing radiation, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
1,109
2
12

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,603 publications
(1,168 citation statements)
references
References 43 publications
45
1,109
2
12
Order By: Relevance
“…Also, the caspase inhibitor Z-YVAD-fmk, a potent inhibitor of caspase-1 (Schumann et al, 1998), inhibited khat-induced cell death (Figure 7). IL-1b is a known substrate for caspase-1 (Kuida et al, 1995). However, the role of caspase-1 in induction of apoptosis is controversial (Nicholson and Thornberry, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the caspase inhibitor Z-YVAD-fmk, a potent inhibitor of caspase-1 (Schumann et al, 1998), inhibited khat-induced cell death (Figure 7). IL-1b is a known substrate for caspase-1 (Kuida et al, 1995). However, the role of caspase-1 in induction of apoptosis is controversial (Nicholson and Thornberry, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of caspase-1 in induction of apoptosis is controversial (Nicholson and Thornberry, 1997). Overexpression of caspase-1 has induced apoptosis in mammalian cells (Miura et al, 1993), whereas mice deficient in IL-1b develop normally, suggesting a less important role of caspase-1 in regulation of cell death during normal embryogenesis (Kuida et al, 1995). On the other hand, thymocytes from IL-1b-deficient mice were found to be resistant to Fas-induced cell death, showing an impairment of the normal regulation of apoptosis in these cells (Kuida et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Fas-and tumor necrosis factor (TNF) receptor-mediated apoptosis is driven by caspase family, because it is suppressed by their inhibitors, including cowpox virus CrmA Enari et al, 1995;Los et al, 1995), baculovirus p35 and tetrapeptide caspase-1 and caspase-3 inhibitors (Enari et al, 1995;Los et al, 1995;Schlegel et al, 1996;Chinnaiyan et al, 1996;Hasegawa et al, 1996). It has also been reported that thymocytes from caspase-1-de®cient mice are resistant to Fas-mediated apoptosis, indicating the direct involvement of caspase-1 itself in this process of thymocyte death (Kuida et al, 1995). Sequential activation of caspase-1(-like) and caspase-3(-like) proteases has been shown to occur in Fas-mediated apoptosis of mouse lymphoma cell line (Enari et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…[12][13][14][15] These mice have a defect in the maturation of proIL-1b and proIL-18 and are resistant to the lethal effect of endotoxins. IL-18 was first described as an endotoxininduced factor that stimulates the production of interferon-g by splenocytes.…”
Section: Caspase-1 and It Substrate Il-1bmentioning
confidence: 99%